PERAN GURU DAN TEMAN SEBAYA DALAM MEMBENTUK SCHOOL WELL BEING SISWA SEKOLAH DASAR - Hana Fatimah; Fajar Sri Utami; Harsono; Masduki (STKIP Subang, 2026)
This study aims to examine the influence of teacher and peer support on the school well-being of elementary students. Using a quantitative approach with an ex post facto correlational design, the research involved 155 students from MI M Tahfidzul Qur’an Matesih, Karanganyar. Data were collected through a Likert-scale questionnaire measuring three variables: teacher support, peer support, and school well-being. The instruments were valid (r > 0.30) and reliable (Cronbach’s Alpha = 0.887). Multiple regression analysis revealed that both teacher support (β = 0.312, p < 0.01) and peer support (β = 0.286, p < 0.01) significantly predicted school well-being. The model explained 32.3% of the variance in school well-being (R² = 0.323). These findings indicate that emotional and social support from teachers, along with positive peer interactions, play a vital role in fostering students’ happiness, sense of belonging, and engagement in school activities. Strengthening these social supports can create a more inclusive and nurturing school environment.